Guidance for programmatic management of latent tuberculosis infection in the European Union/European Economic Area. Issue 1 (17th January 2019) - Rosales-Klintz, Senia; Bruchfeld, Judith; Haas, Walter; Heldal, Einar; Houben, Rein M.G.J.; van Kessel, Femke; Mandelbaum, Mike; Matteelli, Alberto; Migliori, Giovanni Battista; Oordt-Speets, Anouk; Solovic, Ivan; Vašáková, Martina; et al.
Worldwide efforts are being made to end tuberculosis (TB) by 2035 following the ambitions outlined in the World Health Organization (WHO) End TB strategy [1] and the United Nations Sustainable Development Goals [2]. Countries with a low incidence of TB, i.e. less than 10 incident cases per 100 000 population per year, should strive for TB elimination [3]. To this end, timely detection and treatment of latent tuberculosis infection (LTBI) is an important intervention [3]. Currently, the existence and implementation of national strategies including public health interventions targeting LTBI is heterogeneous across the European Union/European Economic Area (EU/EEA) [4]. To support the EU/EEA countries with developing national policies, as well as the planning and implementation of programmatic management of LTBI into national strategies for TB control, the European Centre for Disease Prevention and Control (ECDC) conducted a comprehensive assessment of the available evidence and developed an evidence-based guidance [5]. The guidance, published in October 2018, elaborates on population-level measures for LTBI management tailored to the EU/EAA context and it is complementary to the WHO guidelines [6]. Here, we summarise the process that was followed to develop the guidance and we outline the key components proposed for programmatic management of LTBI, to inform European healthcare professionals. Management of latent tuberculosis infection is crucial to end TB in low-incidence settings http://ow.ly/pEcD30mJ8zL